2021
DOI: 10.3390/cancers13205126
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between KRAS, SRC and YAP Signaling in Pancreatic Cancer: Interactions Leading to Aggressive Disease and Drug Resistance

Abstract: Pancreatic ductal adenocarcinoma (PDAC), the predominant form of pancreatic cancer, remains a devastating disease. The purpose of this review is to highlight recent literature on mechanistic and translational developments that advance our understanding of a complex crosstalk between KRAS, YAP and Src tyrosine kinase family (SFK) in PDAC development and maintenance. We discuss recent studies indicating the importance of RAS dimerization in signal transduction and new findings showing that the potent pro-oncogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 180 publications
(276 reference statements)
0
11
0
Order By: Relevance
“…In addition, YAP contains an SH3-binding domain that can directly bind to the non-receptor tyrosine kinase Src [ 52 ]. Studies also showed that Src activation mediates YAP dysregulation, invasiveness and drug resistance in tumors [ 53 , 54 ]. UM-164 was discovered as a potent Src inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, YAP contains an SH3-binding domain that can directly bind to the non-receptor tyrosine kinase Src [ 52 ]. Studies also showed that Src activation mediates YAP dysregulation, invasiveness and drug resistance in tumors [ 53 , 54 ]. UM-164 was discovered as a potent Src inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Yes-associated protein 1 (YAP1) is a transcriptional coactivator downstream of the Hippo signalling pathway, which is essential for PDAC formation and development 19. YAP1 not only cooperates with KRAS in PDAC initiation but can also substitute KRAS for survival of the most aggressive subtype of advanced PDAC 20–23.…”
Section: Introductionmentioning
confidence: 99%
“…YAP1 not only cooperates with KRAS in PDAC initiation but can also substitute KRAS for survival of the most aggressive subtype of advanced PDAC 20–23. While the Hippo network is a major mechanism that controls YAP activity, recent studies have identified Hippo pathway-independent mechanisms that regulate YAP localisation and activity 19 24. The occurrence and precise significance of other modifications of YAP1 in PDAC remain largely unknown, thus, requiring further experimental work.…”
Section: Introductionmentioning
confidence: 99%
“…Src has been reported to be an important downstream regulator of GABAergic signal transduction [ 17 , 18 ]. Src is commonly expressed in human cancers, including colon, lung, breast, and endometrial tumors [ 19 , 20 ]. Notably, Src is a major component of the processes and pathways that regulate glioblastoma (GBM) tumorigenesis, such as proliferation, invasion, migration, and the epidermal growth factor receptor, Ras/Raf/MEK, and PI3K/AKT pathways [ 2 , 21 ].…”
Section: Introductionmentioning
confidence: 99%